Radiation induced vasculitis of iliac veins: presentation of a case and therapeutic dilemmas - Galanopoulos, Georgios (International Surgery Journal, 2020)
A case of radiation-induced venous stenosis (phlebitis) after pelvic irradiation in a patient with prostate cancer is reported. Progressive swelling of both lower limbs developed due to bilateral external iliac vein stenosis. Conservative treatment with new oral anticoagulants and elastic stockings was conducted with clinical improvement of symptoms. Serial duplex scanning with trimestral frequency reveals no other progression of stenosis and the patient is well 2 years after diagnosis. Lack of data in the current literature makes management of this disease problematic.